THE RELATIONSHIP OF SERVICE QUALITY WITH THE LEVEL OF SATISFACTION OF BPJS OUTPATIENT PATIENTS IN NUHON HEALTH CENTER, NUHON DISTRICT, BANGGAI DISTRICT 2022 - Novitasari, Desi (Jurnal Ilmiah dr. Aloei Saboe, 2024)
The Ministry of Health's policy in efforts to improve the quality of services at first level health facilities, especially Puskesmas, is to issue Regulation of the Minister of Health (Permenkes) of the Republic of Indonesia Number 46 of 2015 concerning Accreditation of Puskesmas, Pratama Clinics, Doctors' Independent Practice Places, and Dentist Independent Practice Places. This aims to ensure that quality improvement, performance improvement and implementation of risk management are carried out continuously at the Community Health Center. The aim of this research is to analyze the relationship between service quality and the level of satisfaction of BPJS outpatients at the Nuhon Community Health Center, Nuhon District, Banggai Regency. The research method used is quantitative research with a cross sectional study design. The sample in this study amounted to 86 respondents. Data analysis used the chi-square test. The research results showed that the results of the Chi-Square test analysis showed results with a value of p = 0.001 < 0.05, which shows that there is a relationship between service quality and the level of satisfaction of BPJS outpatients at the Nuhon Community Health Center, Nuhon District, Banggai Regency. It is hoped that the management of the Nuhon Health Center can carry out management evaluations and improvements to improve the quality of service and should carry out continuous satisfaction surveys to evaluate the performance of health services and the quality of service at the Nuhon Health Center so that it is hoped that it can increase patient satisfaction.